Recycling of metal-fertilized lower continental crust: Origin of non-arc Au-rich porphyry deposits at cratonic edges - Hou, Z.; Zhou, Y.; Wang, R.; Zheng, Y.; He, W.; Zhao, M.; Evans, Noreen; Weinberg, R. (Geological Society of America, 2017)
© 2017 Geological Society of America. Recent studies argue that subduction-modified, Cu-fertilized lithosphere controls the formation of porphyry Cu deposits in orogenic belts. However, it is unclear if and how this fertilization process operates at cratonic edges, where numerous large non-arc Au-rich deposits form. Here we report data from lower crustal amphibolite and garnet amphibolite xenoliths hosted by Ce nozoic stocks that are genetically related to the Beiya Au-rich porphyry deposits along the western margin of the Yangtze craton, China. These xenoliths are thought to represent cumulates or residuals of Neoproterozoic arc magmas ponding at the base of arc at the edge of the craton that subsequently underwent high-pressure metamorphism ca. 738 Ma. The amphibolite xenoliths are enriched in Cu (383-445 ppm) and Au (7-12 ppb), and a few garnet amphibolite xenoliths contain higher Au (6-16 ppb) with higher Au/Cu ratios (2 × 10 -4 to 8 × 10 -4 ) than normal continental crust. These data suggest that metal fertilization of the base of an old arc at the edge of the craton occurred in the Neoproterozoic via subduction modification, and has since been preserved. The whole-rock geochemical and zircon Hf isotopic data indicate that melting of the Neoproterozoic Cu-Au-fertilized low-crustal cumulates at 40-30 Ma provided the metal endowment for the Au-rich porphyry system at the cratonic edge. We therefore suggest that the reactivated cratonic edges, triggered by upwelling of asthenosphere, have the potential to host significant Au ore-forming systems, especially non-arc Au-rich porphyry deposits.